Tackling the challenge of the impact of continuing education: An evidence synthesis charting a global, cross‐professional shift away from counting hours. (29th February 2020) - Bullock, Alison; Kavadella, Argyro; Cowpe, Jonathan; Barnes, Emma; Quinn, Barry; Murphy, Denis
Abstract: Introduction: Health professionals worldwide are required to maintain their knowledge and skills through continuing education. However, there is limited evidence that the accumulation of hours of educational activity enhances practice. The aim of this study was to review evidence of the impact of continuing professional development (CPD), best educational practice and new models of CPD requirements. Methods: We conducted a rapid evidence synthesis, reviewing literature and websites on continuing education for healthcare and non‐healthcare professionals. Results: We extracted data from 184 publications. Evidence of changed practice and improved patient care is uncommon in studies of CPD. What evidence there is suggests that activities are more likely to have impact if a combination of methods is used and if they are aligned with learning needs. Impact is also affected by the learner and their work environment. In terms of CPD requirements, we identified three models: input‐based; outcomes‐based and mixed models. We found a clear shift from quantitative, time‐serving, input‐models to outcomes‐focused models which emphasise the identification of learning needs, selection of educational activity relevant to practice and reflection on practice improvement. Across a range of professions, recently updated CPD regulations no longer require registrants to accumulate CPD hours/points/credits. Conclusion: Outcomes‐based models support registrants' engagement in relevant, meaningful CPD which holds greater potential to positively impact on practice and strengthen patient safety. In funding this study, the UK General Dental Council exemplifies its commitment to reviewing its CPD requirments.